2009
DOI: 10.1111/j.1574-6968.2009.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis ofEscherichia coliO157:H7 bacteriophage ΦV10 and identification of a phage-encoded immunity protein that modifies the O157 antigen

Abstract: Bacteriophage PhiV10 is a temperate phage, which specifically infects Escherichia coli O157:H7. The nucleotide sequence of the PhiV10 genome is 39 104 bp long and contains 55 predicted genes. PhiV10 is closely related to two previously sequenced phages, the Salmonella enterica serovar Anatum (Group E1) phage epsilon15 and a prophage from E. coli APEC O1. The attachment site of PhiV10, like those of its two closest relatives, overlaps the 3' end of guaA in the host chromosome. PhiV10 encodes an O-acetyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…Therefore, AR1 phage has the potential to be used as a bactericidal food additive to prevent contamination with E. coli O157:H7 in the food industry. In addition, several reports have indicated that some antibiotics may increase Shiga-like toxin production, resulting in increased side effects for patients (39,61). Therefore, AR1 could also be used as an alternative therapeutic agent for treating E. coli O157:H7 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, AR1 phage has the potential to be used as a bactericidal food additive to prevent contamination with E. coli O157:H7 in the food industry. In addition, several reports have indicated that some antibiotics may increase Shiga-like toxin production, resulting in increased side effects for patients (39,61). Therefore, AR1 could also be used as an alternative therapeutic agent for treating E. coli O157:H7 infection.…”
Section: Discussionmentioning
confidence: 99%
“…NC_011357; Y. Zhang et al, unpublished data); the enterobacterial phages 933W (64), VT2-Sakai (40,47), Min27 (36,77), and YYZ-2008 (GenBank accession no. NC_011356; Zhang et al, unpublished data), which encode the Stx-like proteins; and the nontoxin-carrying phages phiV10 (61) and JK06 (GenBank accession no. NC_007291; J. Kagan et al, unpublished data).…”
mentioning
confidence: 99%
“…A contig of 39 kb shared similarity with the epsilon15-like Podovirus phiV10 over 63% of its genome length covering virion, lysis, lysogeny and replication genes (Perry et al, 2009) (Fig. 4C).…”
Section: Rtpmentioning
confidence: 98%
“…In the case of all three homologous phages, it is the morphogenic genes which are conserved. Perry and Applegate sequenced the E. coli O157:H7-specifi c phage V10 [ 139 ], misnamed φV10, and showed that it displays considerable sequence similarity to ε15, but lacks the conversion genes of this phage [ 140 ].…”
Section: Epsilon15likevirusmentioning
confidence: 99%